-2=(7y-8y)2+14

Simple and best practice solution for -2=(7y-8y)2+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2=(7y-8y)2+14 equation:


Simplifying
-2 = (7y + -8y) * 2 + 14

Combine like terms: 7y + -8y = -1y
-2 = (-1y) * 2 + 14

Remove parenthesis around (-1y)
-2 = -1y * 2 + 14

Reorder the terms for easier multiplication:
-2 = -1 * 2y + 14

Multiply -1 * 2
-2 = -2y + 14

Reorder the terms:
-2 = 14 + -2y

Solving
-2 = 14 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-2 + 2y = 14 + -2y + 2y

Combine like terms: -2y + 2y = 0
-2 + 2y = 14 + 0
-2 + 2y = 14

Add '2' to each side of the equation.
-2 + 2 + 2y = 14 + 2

Combine like terms: -2 + 2 = 0
0 + 2y = 14 + 2
2y = 14 + 2

Combine like terms: 14 + 2 = 16
2y = 16

Divide each side by '2'.
y = 8

Simplifying
y = 8

See similar equations:

| (9n+4)+(3n^2-0.75)=180 | | -5h-13=-28 | | x^2-70=7x | | -x+5=2(x-8) | | 10x-6=3x-5 | | W-26=12 | | 9x+6y=n | | N+3=15-6 | | 3x-435=2425 | | 32+x+x+90=180 | | -4y+15=39 | | 0=x^2-5x-6.67 | | 8(x-2)+5=6x+2(-4+x) | | 5(x-3)+6=5x+9 | | 9y=6y+36 | | (6x-1)+(13+13)=90 | | 2x^2+8x-46=0 | | (7+m)+m=35 | | An=-5n-5 | | 6=m-39 | | 8x+20=6x+34 | | 2x^2-16+15=0 | | 15=5x+2y | | 4x+30+=5x+10 | | Z-17=-5 | | (6x-1)+(9+9)=90 | | 9(2x+3)=y | | -3y+5=-3y-9 | | 24+15x=50+2x | | 3x+15=4x+1 | | 5x-13=5x+6 | | -4v(v+6)=-16 |

Equations solver categories